2019
DOI: 10.33338/ef.84629
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure and distribution of antennal sensilla of stink bug <i>Arma chinensis</i> (Heteroptera: Pentatomidae)

Abstract: Scanning electron microscopy was used to examine the morphology, ultrastructure, and distribution of antennal sensilla of the stink bug Arma chinensis. Two types of sensilla trichodea (ST1–2), four types of sensilla basiconica (SB 1– 4), one type of sensilla chaetica (SCH), one type of sensilla cavity (SCA) and one type of sensilla coeloconica (SCO) were distinguished on the antennae in both sexes. ST1 and ST2 were absent from the scape and pedicel. SB1 were absent from the scape. SB2 were distributed througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Majority of insect species show presence of Böhm sensilla (Merivee et al, 2000; Ren et al, 2012; Zhang et al, 2014). Böhm sensilla of the antenna of A. chalybaeus fit the description of Schneider (1964) about the sensilla which are often found in the region between the antennal sockets and the scapes, and in the region between the scapes and pedicels.…”
Section: Discussionmentioning
confidence: 99%
“…Majority of insect species show presence of Böhm sensilla (Merivee et al, 2000; Ren et al, 2012; Zhang et al, 2014). Böhm sensilla of the antenna of A. chalybaeus fit the description of Schneider (1964) about the sensilla which are often found in the region between the antennal sockets and the scapes, and in the region between the scapes and pedicels.…”
Section: Discussionmentioning
confidence: 99%
“…So in the discussion below, a set of the antennal sensilla in semiaquatic and several terrestrial bugs have been compared, e.g. Pentatomomorpha, Scutelleridae (Romani and Rossi 2009 ), Pentatomidae (Silva et al 2010 ; Zhang et al 2014 ; Ahmad et al 2016 ) and Coreidae (Gonzaga-Segura et al 2013 ), Cimicomorpha: Miridae (Chinta 1997 ) and Reduviidae (Catalá 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Terminology for the sensilla. The identification of sensilla and the analysis of their features carried out in the present study were based on Altner and Prillinger 26 and Shields 28 , as well as morphological comparisons of antennal sensilla of different species of Heteroptera presented in several papers 39,[41][42][43]52,58,60,62,67 . Sensilla were divided into particular types based on the presence or absence of pores, grooved or smooth surfaces, and flexible or inflexible sockets at the base of the sensilla.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…So far, the morphology and ultrastructure of the receptors in the terrestrial heteropteran taxa have been studied on several species within individual families, with particular attention paid to species harmful to agriculture or of medical importance. Most research was concerned with the typical morphological structure and function of sensilla in pentatomid bugs 29,[36][37][38][39][40][41][42][43] . There are also numerous articles regarding the antennal sensilla in hematophagous species belonging to the family Reduviidae [44][45][46][47][48][49] , which showed that the type of poral system of antennal chemoreceptors has significant differences among species.…”
mentioning
confidence: 99%